Iron accumulation in the heart of a patient with primary hemochromatosis type I (homozygous C282Y mutation of the HFE gene) - M.H.E. Laouar; R. V. Ponomarev; M. A. Kanunnikova; E. S. Neronova; N. T. Tynybekova; I. V. Tremzina; M. M. Malagina; A. B. Leonova; V. А. Baranova; E. O. Saakyants; A. A. Duktovskaya; P. A. Ovcharenko; et al. (Clinical Medicine (Russian Journal), 2026)
Primary hemochromatosis results from pathogenic variants in several genes that can lead to increased iron stores in the body, with excess iron deposited in various organs including the liver, pancreas, and heart. Primary hemochromatosis is associated with homozygosity for the HFE p.Cys282Tyr mutation in 80% of cases. However, rare cases of hemochromatosis (nonHFE hemochromatosis) can be caused by pathogenic variants in other genes (such as HJV, HAMP, TFR2, and SLC40A1). Deposition of excess iron in parenchymal tissues leads to cellular dysfunction and clinical manifestations of the disease. The most commonly aff ected organs are the liver, pancreas, joints, skin, pituitary gland, and heart. Iron-overload cardiomyopathy is systolic or diastolic dysfunction of the heart caused by excess iron deposition, resulting in chronic heart failure. The gold standard for diagnosing primary hemochromatosis is genetic testing, which should be performed in all patients suspected of having this pathology after excluding secondary causes of iron overload. The mainstay of hemochromatosis therapy is therapeutic phlebotomy and iron chelation. The article presents a clinical case of a patient with primary hemochromatosis and a history of very high serum ferritin levels, which led to iron accumulation in the heart.